Dual process model of farmers’ mindfulness and sustainable economic behavior: Mediating role of mental health and emotional labor - Qiu, Yue; Zhang, Yumeng; Liu, Meihang (Frontiers in Psychiatry, 2022)
Mindful awareness of our interconnection with the natural environment could help to redeem our lost environmentally entrenched identity and help us to act more sustainably, concluding the predictable gaps between mindfulness and sustainable behavior. We propose more precisely that mindful attentiveness may be essential to establishing sustainable economic behavior through understanding emotional labor and enhanced mental health. Likewise, with an ever-rising concern related to mental health and emotional labor, recent industrialization and commoditization of agricultural products have stressed the need for mindfulness, and causing sustainable economic behavior of farmers that is imminent. Hence, the study will not only explore the connection between mindfulness and sustainable economic behavior, but there is a need to examine the mediating role of emotional labor and the mental health of farmers in China. The study selected the farmers because mindful awareness, emotional labor, and mental health of a farmer can significantly contribute to sustainable economic behavior and bring a connection with the natural environment. The data of 358 responses were analyzed using SPSS-AMOS. The results revealed that mindfulness, mental health, and emotional labor have a significant connection with the sustainable economic behavior of farmers in China. The results also indicated that mental health and emotional labor mediate between mindfulness and sustainable economic behavior. The results set the tone for the policy-makers to create awareness among all the stakeholders about the importance of mindfulness to help farmers manage their emotional labor and mental health for better, sustainable performance outcomes.